Intervensi Non Farmakologi untuk Menurunkan Kecemasan dan Ketakutan Persalinan pada Trimester III Kehamilan (Journal of Telenursing (JOTING), 2024)
This study aims to identify non-pharmacological interventions that can reduce anxiety and fear during childbirth in the third trimester of pregnancy. Using the PRISMA method, the research method used is a systematic review through searching 6 (six) databases, namely ProQuest, Scopus, Pubmed, Science Direct, and Taylor & Francis. The results of research from 11 articles included in the analysis show that non-pharmacological interventions that can reduce pregnant women's anxiety levels regarding pregnancy and childbirth are providing education and training in preparation for childbirth carried out face to face (P < 0.001), Iyengar yoga (P < 0 .05), and the application of lavender oil as aromatherapy (P